An ultra high-efficiency droplet microfluidics platform using automatically synchronized droplet pairing and merging. Issue 21 (16th September 2020) - Zhang, Han; Guzman, Adrian R.; Wippold, Jose A.; Li, Yuwen; Dai, Jing; Huang, Can; Han, Arum
Abstract : The integrated droplet platform combines curved microstructures that allow high-efficiency (99.9%) reflow of droplets and a droplet cleaving that automatically synchronizes paired droplets enabling high-efficiency (99.9%) downstream merging. Abstract : Droplet microfluidics systems hold great promise in their ability to conduct high-throughput assays for a broad range of life science applications. Despite their promise in the field and capability to conduct complex liquid handling steps, currently, most droplet microfluidic systems used for real assays utilize only a few droplet manipulation steps connected in series, and are often not integrated together on a single chip or platform. This is due to the fact that linking multiple sequential droplet functions within a single chip to operate at high efficiency over long periods of time remains technically challenging. Considering sequential manipulation is often required to conduct high-throughput screening assays on large cellular and molecular libraries, advancements in sequential operation and integration are required to advance the field. This current limitation greatly reduces the type of assays that can be realized in a high-throughput droplet format and becomes more prevalent in large library screening applications. Here we present an integrated multi-layer droplet microfluidic platform that can handle large numbers of droplets with high efficiency and minimum error. The platform combines two-photon photolithography-fabricated curved microstructures that allow high-efficiency (99.9%) re-flow of droplets and a unique droplet cleaving that automatically synchronizes paired droplets enabling high-efficiency (99.9%) downstream merging. We demonstrate that this method is applicable to a broad range of droplet sizes, including relatively large droplet sizes (hundreds of micrometers in diameter) that are typically more difficult to manipulate with high efficiency, yet are required in many cell assay applications requiring large organisms or multiple incubation steps. The utility of this highly efficient integrated droplet microfluidic platform was demonstrated by conducting a mock antibiotic screening assay against a bacterial pathogen. The approach and system presented here provides new avenues for the realization of ultra-high-efficiency multi-step droplet microfluidic systems with minimal error.